Suppressing depolarization by tail substitution in an organic supramolecular ferroelectric - Urbanavičiūtė, Indrė; Bhattacharjee, Subham; Biler, Michal; Lugger, Jody A. M.; Cornelissen, Tim D.; Norman, Patrick; Linares, Mathieu; Sijbesma, Rint P.; Kemerink, Martijn (Physical chemistry, chemical physics, 2019)
Despite being very well established in the field of electro-optics, ferroelectric liquid crystals so far lacked interest from a ferroelectric device perspective due to a typically high operating temperature, a modest remnant polarization and/or poor polarization retention. Here, we experimentally demonstrate how simple structural modification of a prototypical ferroelectric liquid-crystal benzene-1,3,5-trisamide (BTA) - introduction of branched-tail substituents - results in materials with a wide operating temperature range and a data retention time of more than 10 years in thin-film solution-processed capacitor devices at room temperature. The observed differences between linear- and branched-tail compounds are analyzed using density functional theory (DFT) and molecular dynamics (MD) simulations. We conclude that morphological factors like improved packing quality and reduced disorder, rather than electrostatic interactions or intra/inter-columnar steric hindrance, underlay the superior properties of the branched-tailed BTAs. Synergistic effects upon blending of compounds with branched and linear side-chains can be used to further improve the materials’ characteristics.
Gesehen am 26.11.2019